Homeland security and terrorism in Nigeria: crises, climate change, and counterterrorism - Folarin, Sheriff (Lexington Books, 2024)
"Tracing the origins and examining the dimensions of homeland security challenges, this book analyzes these crises, deepens understanding of the Nigerian security dilemma, and seeks pathways to a more secure homeland"--